Spark : the revolutionary new science of exercise and the brain - Ratey, John J., 1948-; Hagerman, Eric. (London : Quercus, 2010)
Explores the mind-body connection, presenting startling research to prove that exercise is truly our best defense against everything from depression to ADD to addiction to aggression to menopause to Alzheimer's.
Introduction: making the connection -- Welcome to the revolution: a case study on exercise and the brain -- Learning: grow your brain cells -- Stress: the greatest challenge -- Anxiety: nothing to panic about -- Depression : move your mood -- Attention deficit: running from distraction -- Addiction: reclaiming the biology of self-control -- Hormonal changes: the impact on women's brain health -- Aging: the wise way -- The regimen: build your brain -- Afterword: fanning the flames.
Includes index.
First published in Great Britain in 2009 by Quercus.
Keywords: Exercise -- Physiological aspects; Exercise -- Psychological aspects; Mind and body; Brain